PERBEDAAN KADAR KOLESTEROL TOTAL PASIEN PENYAKIT JANTUNG KORONER DENGAN DIABETES MELITUS DAN TIDAK DIABETES MELITUS - Sari, Desy Puspita; Pratiwi, Dewi Indah Noviana; Yuliana, Ida (Pendidikan Dokter Universitas Lambung Mangkurat, 2015)
Coronary heart disease (CHD) is the major cause of deathÂ in the world.CHD is constriction or occlusion of arteries which supply blood flow to heart muscle with the result lack of blood oxygen supply because atherosclerosis process or spasm or both. The incidence of atherosclerosis at large artheries increase in diabetes melitus (DM) patients.DM is a major risk factor for CHD pathogenesis. One of risk factor for CHD in DM patients is theÂ increase ofÂ cholesterol level, a lipid metabolism abnormality.This study aimed to analyze the comparation of total cholesterol between CHD with DM and without DM in RSUD Ulin Banjarmasin period June-August 2014. This study was analytic observational with cross-sectional approach and used consecutive sampling. The total ofÂ sample was 60 patients which contain 30 CHD with DM patients and 30 CHD without DM patients. The result showed the mean of CHD with DM patientsâs cholesterol total level was 230,50 mg/dL and the mean of CHD without DM patientâs was 197,47 mg/dL.The data anlysis result using independent T-test showed that there is significant difference of cholesterol total level between CHD with DM patients and CHD witout DM patients (p=0,007) in RSUD Ulin Banjarmasin.Â Keywords: coronary heart disease (CHD), diabetes melitus (DM), total cholesterol